2020
DOI: 10.1088/1674-1056/abad22
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CdS films synthesized by different methods on the photovoltaic performance of CdTe/CdS thin film solar cells*

Abstract: The cadmium sulphide (CdS) film is grown on cadmium telluride (CdTe) nanorods (NRs) arrays by different methods such as chemical bath deposition (CBD), magnetron sputtering (MS), and homogenous precipitation (HP) techniques. The impact of various deposition methods is explored in detail on the growth of CdTe/CdS composite film, the CdTe/CdS interface property, and solar cell efficiency. Compared to the CBD and HP methods, the MS method can improve the growth of the CdS on CdTe NRs with high crystalline quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…A very relevant field where most of the semiconductors obtained by CBD are implemented is the photovoltaic energy field. For example, a very reported application for CdS thin films is the use as a window layer in the CdS/CdTe solar cell structure [73][74][75]. Jun Wang et al [73] reported a comparative study where different techniques were used for the CdS fabrication: magnetron sputtering, homogeneous precipitation and CBD.…”
Section: Applications Related To Cbd-grown Materials and Comparison W...mentioning
confidence: 99%
See 1 more Smart Citation
“…A very relevant field where most of the semiconductors obtained by CBD are implemented is the photovoltaic energy field. For example, a very reported application for CdS thin films is the use as a window layer in the CdS/CdTe solar cell structure [73][74][75]. Jun Wang et al [73] reported a comparative study where different techniques were used for the CdS fabrication: magnetron sputtering, homogeneous precipitation and CBD.…”
Section: Applications Related To Cbd-grown Materials and Comparison W...mentioning
confidence: 99%
“…For example, a very reported application for CdS thin films is the use as a window layer in the CdS/CdTe solar cell structure [73][74][75]. Jun Wang et al [73] reported a comparative study where different techniques were used for the CdS fabrication: magnetron sputtering, homogeneous precipitation and CBD. The effect of change of reactants in the chemical bath and the use of thermal annealing have been also explored in terms of the CdS/CdTe solar efficiency [74,75].…”
Section: Applications Related To Cbd-grown Materials and Comparison W...mentioning
confidence: 99%
“…1(a)), a hole barrier is formed in back contact due to mismatch of work function. [5,6] Many researchers have proved that copper-doped zinc telluride (ZnTe:Cu) is an ideal back contact material (Fig. 1(b)).…”
Section: Introductionmentioning
confidence: 99%